Effect of cognitive entry characteristics on students' affective outcome in bearing mathematics (2007)
Several studies have confirmed poor attitude of students towards mathematics and the attracted consequences. Since attitude is confirmed to be alterable, efforts of researchers are expected to be directed towards improvement of students' attitude toward this dreaded subject. This informed the investigation of the main and interaction effects of the cognitive entry characteristics (CEC), aptitude and gender on students' attitude towards Bearing in Mathematics. The study adopted a quasi-experimental pretest-posttest research design. Three hundred and thirty two SS 2 students were involved in the study. The sample was drawn using multi-stage sampling technique from public co-educational secondary schools in three offive local government areas in Ibadan Metropolis. The instruments used for data collection were the Test of Spatial Reasoning adopted from Barrett and Williams, (1997) (r = 0.92), Numerical Reasoning Test adapted from Barrett and Williams, (1997) (r = 0.75), Bearing Attitude Scale (r = 0.81) and Diagnostic Tests The data collected were analysed using ANCO VA and MCA. CEChas significant main effect (P<O. 05) but gender and aptitude had no significant main effects on students' attitudes toward bearing. Also, there were no first and second order interactions effects of CEC, aptitude and gender, on students' attitudes toward bearing. Cognitive Entry Characteristics accounted for a high degree of variation in students' affective outcome in Bearing. This has implications for education, especially the curriculum experts and classroom 'teachers, particularly on the need for learning sequence and enhancement activities. which have been found to promote better attitude to mathematics learning in the classroom